Proceedings of the 2nd Annual Civic Education Conference (ACEC 2019) 2020
DOI: 10.2991/assehr.k.200320.070
|View full text |Cite
|
Sign up to set email alerts
|

Reformulating Civic Education as Political Education in Indonesia in the Convergence Era

Abstract: The purpose of writing this article is to reformulate Civic Education as a political education in Indonesia in the era of convergence. The research method used in this article was the library research. The results of the study show; First Civic Education becomes an instrument in political education in the era of convergence. Secondly, to formulate Civic Education as a political education in Indonesia is basically not only meant to make the citizens possess the political knowledge and arouse political participa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 59 publications
0
6
0
Order By: Relevance
“…In line with these, Based on interviews with informants, it was found that providing an understanding of the legal perspective for students at STKIP Pasundan was an attempt to provide an understanding of the function of law in national development as a regulatory tool or means of development in the sense of channeling the desired direction of human activity towards renewal. In line with these findings, Hidayah et al (2020) emphasized that understanding the function of law is a means of educating citizens because, currently, reforms have occurred in various fields. Furthermore, Francis & Fraga (2023) stated that world trends have changed drastically.…”
Section: Strengthening National Identity In Welcoming the 2045 Indone...mentioning
confidence: 65%
“…In line with these, Based on interviews with informants, it was found that providing an understanding of the legal perspective for students at STKIP Pasundan was an attempt to provide an understanding of the function of law in national development as a regulatory tool or means of development in the sense of channeling the desired direction of human activity towards renewal. In line with these findings, Hidayah et al (2020) emphasized that understanding the function of law is a means of educating citizens because, currently, reforms have occurred in various fields. Furthermore, Francis & Fraga (2023) stated that world trends have changed drastically.…”
Section: Strengthening National Identity In Welcoming the 2045 Indone...mentioning
confidence: 65%
“…Success hinges on the dedication of educational institutions and educators. Civic Education contributes to societal welfare and equality, requiring dynamic citizenship (Hidayah et al, 2020;Li et al, 2020). Isin and Turner (2012) highlight the interdisciplinary nature of citizenship studies, addressing themes from welfare to international relations.…”
Section: Introductionmentioning
confidence: 99%
“…Various public concerns about the fading of national identity in this globalization era demand quick and appropriate solutions. Reconstruction of civic education, in this case, is one of the essential alternatives that is promoted besides increasing overall pedagogic abilities (Hidayah et al, 2020;Jayadiputra et al, 2020;Kadiwal & Jain, 2021;Komalasari & Saripudin, 2017). The reconstruction of civic education to strengthen national identity is also based on the consideration that a strong national identity will foster strong nationalism and encourage the political participation of young citizens.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In today's situation, many changes are faced, such as in interaction, communication patterns, and adaptation patterns In the context of a change (Yuen, 2016). Civic education can be a benchmark in analyzing citizens' intelligence (Hidayah et al, 2020).…”
Section: Introductionmentioning
confidence: 99%